Novel 2-(5-Aryl-4,5-Dihydropyrazol-1-yl)thiazol-4-One as EGFR Inhibitors: Synthesis, Biological Assessment and Molecular Docking Insights - Al-Warhi T; El Kerdawy AM; Said MA; Albohy A; Elsayed ZM; Aljaeed N; Elkaeed EB; Eldehna WM; Abdel-Aziz HA; Abdelmoaz MA (Drug Design, Development and Therapy, 2022)
Tarfah Al-Warhi,1 Ahmed M El Kerdawy,2,3 Mohamed A Said,4 Amgad Albohy,5 Zainab M Elsayed,6 Nada Aljaeed,1 Eslam B Elkaeed,7 Wagdy M Eldehna,8,9 Hatem A Abdel-Aziz,10 Miral A Abdelmoaz11 1Department of Chemistry, College of Science, Princess Nourah Bint Abdulrahman University, Riyadh, Saudi Arabia; 2Department of Pharmaceutical Chemistry, Faculty of Pharmacy, Cairo University, Cairo, Egypt; 3Department of Pharmaceutical Chemistry, School of Pharmacy, Newgiza University (NGU), Newgiza, Cairo, Egypt; 4Department of Pharmaceutical Chemistry, Faculty of Pharmacy, Egyptian Russian University, Badr City, Cairo, 11829, Egypt; 5Department of Pharmaceutical Chemistry, Faculty of Pharmacy, The British University in Egypt (BUE), El-Sherouk City, Cairo, 11837, Egypt; 6Scientific Research and Innovation Support Unit, Faculty of Pharmacy, Kafrelsheikh University, Kafrelsheikh, Egypt; 7Department of Pharmaceutical Sciences, College of Pharmacy, Almaarefa University, Riyadh, 13713, Saudi Arabia; 8School of Biotechnology, Badr University in Cairo, Badr City, Cairo, 11829, Egypt; 9Department of Pharmaceutical Chemistry, Faculty of Pharmacy, Kafrelsheikh University, Kafrelsheikh, 33516, Egypt; 10Department of Applied Organic Chemistry, National Research Center, Dokki, Giza, 12622, Egypt; 11Department of Pharmaceutical Chemistry, Faculty of Pharmacy, Sinai University, Kantra, EgyptCorrespondence: Wagdy M Eldehna, Department of Pharmaceutical Chemistry, Faculty of Pharmacy, Kafrelsheikh University, Kafrelsheikh, 33516, Egypt, Tel +201068837640, Email wagdy2000@gmail.comIntroduction: Epidermal growth factor receptor (EGFR) regulates several cell functions which include cell growth, survival, multiplication, differentiation, and apoptosis. Currently, EGFR kinase inhibitors are of increasing interest as promising targeted antitumor therapeutic agents.Methods: Different thiazolyl-pyrazoline derivatives ( 7a-o) were synthesized and were first tested for anti-proliferative effect towards the A549 lung cancer cell line and the T-47D breast cancer cell line in MTT assay. Thereafter, thiazolyl-pyrazolines ( 7b, 7g, 7l, and 7m) were subsequently evaluated for their PK inhibition for EGFR. Moreover, representative promising derivatives ( 7g and 7m) in cytotoxic and PK inhibition assays were tested to investigate their impact on the apoptosis and cell cycle phases in T-47D cells in order to explore more insights into the antitumor actions of the target thiazolyl-pyrazolines. Furthermore, docking studies were accomplished to evaluate the patterns of binding of thiazolyl-pyrazolines 7b, 7g, 7l, and 7m in the EGFR active pocket (PDB ID: 1M17).Results: Testing the thiazolyl pyrazoline compounds 7a-o on A549 and T-47D cell lines showed IC50 arrays between 3.92 and 89.03 μM, and between 0.75 and 77.10 μM, respectively. Also, the tested thiazolyl-pyrazolines ( 7b, 7g, 7l, and 7m) demonstrated significant sub-micromolar EGFR inhibitory actions with IC50 values 83, 262, 171 and 305 nM, respectively, in comparison to erlotinib (IC50 =57 nM).Discussion: Generally, it was observed that the tested thiazolyl pyrazolines showed more potent antiproliferative activity toward breast cancer cells T-47D than toward lung cancer cell lines A549. In particular, thiazolyl pyrazolines 7g and 7m showed the best activity against A549 cells (IC50 = 3.92 and 6.53 μM) and T-47D cells (IC50 = 0.88 and 0.75 μM). Compounds 7g and 7m provoked a sub-G1 phase arrest and cell apoptosis which are in agreement with the expected outcome of EGFR inhibition. Finally, the molecular docking of 7g and 7m in the active site of EGFR revealed a common binding pattern similar to that of erlotinib which involves the accommodation of the 1,3 thiazol-4-one ring and pyrazoline ring of target compounds in the binding region of erlotinib’s quinazoline ring and anilino moiety.Keywords: antitumor, EGFR inhibitors, pyrazolo, molecular docking, breast cancer, lung cancer